2000
DOI: 10.1023/a:1008972518019
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The effects of suspected endocrine disrupting chemicals on freshwater and marine prosobranch species were analysed in laboratory experiments. In this first publication, the responses of the freshwater snail Marisa cornuarietis and of the marine prosobranch Nucella lapillus to the xeno-estrogenic model compounds bisphenol A (BPA) and octylphenol (OP) are presented at nominal concentration ranges between 1 and 100 micrograms/L. Marisa was exposed during 5 months using adult specimens and in a complete life-cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 251 publications
(35 citation statements)
references
References 20 publications
3
29
1
2
Order By: Relevance
“…108 Com relação aos ftalatos, Singh e Li reportaram vinte doenças associadas à exposição a três principais compostos (DnOP, BBP e DEHP), incluindo disfunções no sistema endócrino, genital e uroló-gico, complicações no fígado e doenças cardiovasculares. 139 Outros estudos mostraram que a exposição de diferentes organismos frente aos interferentes endócrinos levaram à ocorrência de efeitos como a feminização de peixes, [140][141][142][143][144][145][146][147][148][149] alterações no desenvolvimento de moluscos e anfíbios, [150][151][152][153][154] disfunções no metabolismo da testosterona em Daphnias 155,156 e o desenvolvimento anormal de órgãos em diferentes organismos aquáticos. 19,146,149,150,157,158 Na Índia, após observarem o declínio de cerca de 95% da quantidade de uma espécie de urubus (Oriental white-backed vulture) na década de 90, Oaks e colaboradores apresentaram fortes evidencias de que as doenças renais que afetaram os animais foram decorrentes da ingestão de resíduos de diclofenaco presentes nas carcaças de búfalos e cabras tratados com o fármaco.…”
Section: Efeitos Relacionados à Presença De Compostos Interferentes Eunclassified
“…108 Com relação aos ftalatos, Singh e Li reportaram vinte doenças associadas à exposição a três principais compostos (DnOP, BBP e DEHP), incluindo disfunções no sistema endócrino, genital e uroló-gico, complicações no fígado e doenças cardiovasculares. 139 Outros estudos mostraram que a exposição de diferentes organismos frente aos interferentes endócrinos levaram à ocorrência de efeitos como a feminização de peixes, [140][141][142][143][144][145][146][147][148][149] alterações no desenvolvimento de moluscos e anfíbios, [150][151][152][153][154] disfunções no metabolismo da testosterona em Daphnias 155,156 e o desenvolvimento anormal de órgãos em diferentes organismos aquáticos. 19,146,149,150,157,158 Na Índia, após observarem o declínio de cerca de 95% da quantidade de uma espécie de urubus (Oriental white-backed vulture) na década de 90, Oaks e colaboradores apresentaram fortes evidencias de que as doenças renais que afetaram os animais foram decorrentes da ingestão de resíduos de diclofenaco presentes nas carcaças de búfalos e cabras tratados com o fármaco.…”
Section: Efeitos Relacionados à Presença De Compostos Interferentes Eunclassified
“…In contrast, there has been considerably more research investigating the effects of BPA in molluscs, where most has been focused on gastropods and bivalves. Oehlmann et al (2000) have reported that exposure of ramshorn snails (Marisa cornuarietis) to BPA induced a superfeminization syndrome at all nominal concentrations tested (1, 5, 25, 100 mg BPA l egg production outside the main spawning season and increased female mortality (13.3-15.7% in exposed snails compared with control mortality of 3.8%). Effects were concentration dependent (except for mortality) and statistically significant at every test concentration.…”
mentioning
confidence: 99%
“…[179] Pimephales promelas Schlupfrate 16 Hahn et al [180] Chironomus riparius Vitellogenin 1 Pascoe et al [181] Hydra vulgaris Polypenhabitus 42 Segner et al [162] Danio rerio Vitellogenin 375 Segner et al [162] Hydra vulgaris Regeneration 1 Segner et al [162] Gammarus pulex Paarbildung 830 Segner et al [162] Chironomus riparius Häutung 1000 Van der Hoeven [182] Marisa cornuarietis Eiablage 2,1 (EC10) Oehlmann et al [183] Marisa cornuarietis Super-Weibchen (endokrine Wirkung) 0,0079 0,0139 (EC 10 ) Nucella lapillus Forbes et al [184] Marisa cornuarietis Reproduktion 640 Wachstum Weibchen 640 Wachstum Männchen 1 Bromdichlormethan Toussaint et al [185] Oryzias latipes Histopathologie (Leber) 1424 Nonylphenol Schwaiger et al [186] Cyprinus carpio Blutparameter 1-5 5-10 Histopathologie Leber, Niere 15 Hahn et al [180] Chironomus riparius Dotterprotein 1,9 Schwaiger et al [187] Oncorhynchus mykiss Vitellogenin 1 Schlupfrate 10 Seki et al [188] Oryzias latipes Geschlechtsdiff erenzierung 11,6 Vitellogenin Lahnsteiner et al [189] Oncorhynchus mykiss Spermatogenese 0,13 Ei-Entwicklung 0,28 Lee & Choi [190] Chironomus riparius div. Biomarker 1 (Stressproteine, DNA-Schäden) Schubert et al [191] Salmo trutta Vitellogenin 0,111 Octylphenol Jobling et al [192] Oncorhynchus mykiss Vitellogenin 4,8 Oehlmann et al [178] Marisa cornuarietis Nucella lapillus Super-Weibchen 1 (endokrine Wirkung) Andersen et al [193] Acartia tonsa (Copepoda) Larvalentwicklung 13 Seki et al [188] Oryzias latipes Geschlechtsdiff erenzierung 11,4 Vitellogenin Karels et al [194] Cyprinodon variegatus Vitellogenin 11,5 Bjerregaard et al [173] Salmo trutta …”
Section: Carassius Auratusunclassified